Building up Leadership Skills in Vulnerable Social Groups. Case Study in Bipolar Disorder and Psychoeducation Contribution - Antonopoulou, Hera (Technium Business and Management, 2023)
The focus of this study is on the psychoeducation therapy program, which is widely utilized in the field of mental health. The study aims to examine the effects of this program on individuals who are dealing with a mental disease. The main aim is to establish a support network for oneself and one’s immediate social connections. Moreover, the text explicitly acknowledges bipolar disorder, a psychiatric ailment distinguished by alternating spells of elevated or irritable mood and melancholy. To streamline the examination of these issues, a determination was taken to divide them into two separate elements. The introductory portion of the text provides an explanation of the importance of psychoeducational therapy, specifically within the framework of bipolar disorder. Following this, the subsequent phase of this research suggests the implementation of a psychoeducational program consisting of carefully designed sessions, considering the findings and analysis. The continuous examination encompasses both the procedural aspects and the contextual factors. This study emphasizes the significance of recognizing individuals above the limitations imposed by their circumstances, so exposing the wide potential for leadership within marginalized social groups. The results of the study support the notion of adopting a more comprehensive and inclusive strategy for cultivating leadership skills, emphasizing the significance of psychoeducation as a catalyst for personal growth and change.